Dispositional Self-Construal Modulates Neural Representation of Self: An ERP Study - Chen, Jie; Yuan, Panpan; Cai, Yaohan; Liu, Cuihong; Li, Wenjie (Frontiers in Psychology, 2020)
This study aimed to investigate the influence of dispositional self-construal on self-related processing. Event-related potentials (ERPs) were recorded for participants’ own and the famous person’s names in a three-stimulus oddball task. Results showed increased P2 and P3 amplitudes induced by one’s own than by the famous person’s names in both independent and interdependent self-construal groups. However, no N2 amplitude differences were found between one’s own and the famous person’s names in both groups. Moreover, the strength of P2 effect (one’s own vs. the famous person’ s name) was stronger in independent than in interdependent self-construal group, whereas the P3 effect was similar between these two groups. Thus, these findings might reflect fast modulation of dispositional self-construal on self-related processing.